Narasimha carved on the external wall of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
Narasimha is carved on the external wall of the mandapa (pillared hall), though time has weathered its intricate details. This depiction portrays the fourth incarnation of Vishnu, showcasing his formidable aspect with a lion’s visage atop a human form. Despite the erosion of many arms, Narasimha’s attributes are intact. In his upper hands, he holds a chakra (discus) and a shankha (conch shell), symbols of cosmic order and divine sound. His frontal hands are depicted in the act of subduing an asura (demon), although the figure is heavily damaged. He is adorned with jewels and a long garland. Additionally, a figure resembling Varaha is carved at the bottom left.